Interior Poverty in the Thought of Meister Eckhart as an Inspiration for Contemporary Sustainable Consumption - Łukaszewska, Katarzyna (Studia Ecologiae et Bioethicae, 2023)
This article aims at presenting Meister Eckhart’s category of interior poverty as a contemporary proposal for the issue of sustainable consumption. Attempts to appropriate the discourse almost exclusively by means of economic optics seem unfounded in this context. Indeed, the issue of sustainable consumption is multifaceted, hence the idea to look at it from the perspective of the original thought of Meister Eckhart, who remains remarkably contemporary in his views on interior poverty. Renunciation in the form of depriving man of desires above all and not of things themselves remains a challenge to the intemperance and excesses of our everyday choices; moreover, the positioning of duty in being rather than action, in other words, by Meister Eckhart, is closer to our times than we used to think and remains an inspiring factor for contemporary searches for the core of personal interior preparation within a context of intemperate consumption.